Bulgaria : Staff Report for the 2002 Article IV Consultation and First Review Under the Stand-By Arrangement and Request for Waiver of Nonobservance and Waiver of Applicability. (IMF Staff Country Reports; Country Report ;, 2002)
This paper assesses Bulgaria's 2002 Article IV Consultation, First Review Under the Stand-By Arrangement (SBA), and a Request for Waiver of Non-observance and Waiver of Applicability. The authorities' structural reform program is ambitious, but implementation needs to be stepped up. In particular, although the energy sector reform program aims appropriately at privatization and increased competition, delays in restructuring district heating companies and increasing energy prices toward cost-recovery levels need to be overcome. The IMF staff supports the authorities' request for completion of the first program review under the SBA.